Phenethylisothiocyanate Potentiates Platinum Therapy by Reversing Cisplatin Resistance in Cervical Cancer - Mahapatra, Elizabeth; Sengupta, Debomita; Kumar, Ravindra; Dehury, Budheswar; Das, Salini; Roy, Madhumita; Mukherjee, Sutapa (Frontiers in Pharmacology, 2022)
Acquired cisplatin resistance in cervical cancer therapy is principally caused by reduction in intracellular drug accumulation which is exerted by hyperactivation of oncogenic PI3K/Akt signalling axis and overexpression of cisplatin-exporter MRP2 along with prosurvival-effectors NFκB and IAPs in cervical cancer cells. These activated prosurvival signalling cascades drive drug-efflux and evasion of apoptosis for rendering drug-resistant phenotypes. Our study challenges PI3K/Akt axis in cisplatin-resistant cervical cancer scenario with phenethylisothiocyanate (PEITC) for chemosensitization of SiHaR, a cisplatin resistant sub-line of SiHa and 3-methylcholanthrene induced cervical cancer mice models. SiHaR exhibited higher MRP2, p-AktThr308, NFκB, XIAP, and survivin expressions which cumulatively compromised cisplatin retention capacity and accumulated PEITC better than SiHa. SiHaR appeared to favour PEITC uptake as its accumulation rates were found to be positively-correlated with MRP2 expressions. PEITC treatment in SiHaR for 3h prior to cisplatin exposure revived intracellular platinum levels, reduced free GSH levels, generated greater ROS and altered mitochondrial membrane-potential compared to SiHa. Western blot, and immunofluorescence results indicated that PEITC successfully downregulated MRP2 in addition to suppressing p-AktThr308, XIAP, survivin and NFκB expressions. In mice models, administration of 5mg/kg body-weight PEITC priming dosage prior to treatment with 3mg/kg body-weight of cisplatin, remediated cervical histology and induced tumour regression in contrast to the group receiving same dosage of cisplatin only. This suggested PEITC as a potential chemosensitizing agent in light of acquired cisplatin resistance in cervical cancer and established its candidature for Phase I clinical trial.